Wie multiplizieren Sie # ((5x) / (3x +1)) - (1 / (9x + 3)) = (7/6) #?

# (9x +3) # kann als geschrieben werden # 3 (3x + 1) # und 6 kann als geschrieben werden # 3 xx 2 #

Die L.C.M von # (3x + 1), 3 (3x + 1) # und # 3 xx 2 # # = 6 (3x + 1) #

# (5x xx 6) / (6xx (3x + 1) ## - (1 xx2) / (6xx (3x + 1) # # = (7 xx (3x + 1)) / (6 xx (3x + 1)) #

# (30x - 2) / (6xx (3x + 1) # # = (21x +7) / (6xx (3x + 1) #

# (30x - 2) / abbrechen (6xx (3x + 1) # # = (21x +7) / abbrechen (6xx (3x + 1) #

# 9x = 7 + 2 #

# x = 9/9 #

# x = 1 #